1990
DOI: 10.1149/1.2086333
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of 10 nm Stacked Insulator on Polycrystalline Silicon in Planar and Trench Capacitors

Abstract: The reliability of three types of stacked insulating films (ONO, ON, NO) with thicknesses of 10 nm and below deposited on highly doped polysilicon are compared. It is shown that the doping process of the underlaying polysilicon plays an important role in the dielectric breakdown behavior. Evaluation of I-E characteristics from voltage ramp measurements demonstrates the influence of top and bottom oxide thickness. Under NO double layers generally a native oxide is found. This leads to similar reliability result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…[12][13][14][15][16] A transport analysis of experimental data allows us to point out the role of each single layer dielectric in the multilayer structure conduction mechanism. In particular, we claim that the electrical transport through the analyzed multilayer structures can be described in terms of conduction mechanisms of isolated single-layer dielectrics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14][15][16] A transport analysis of experimental data allows us to point out the role of each single layer dielectric in the multilayer structure conduction mechanism. In particular, we claim that the electrical transport through the analyzed multilayer structures can be described in terms of conduction mechanisms of isolated single-layer dielectrics.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental data, reported in the literature, have shown that silicon nitride is more conductive than silicon dioxide for a given electric field, 12,13 the current-field characteristic of the nitride/oxide dual-layer film with an oxide cathode ͑called hereafter ON͒ is very similar to that of a single oxide film, 13,14 the nitride/ oxide dual-layer film with a nitride cathode ͑called hereafter NO͒ is less conductive than the ON case for a given electric field, 13,14 and finally, the tri-layer ONO current-field characteristics are similar to the NO structure 13,15 and are strongly influenced by the thickness of the anode side oxide. 15,16 The electrode-limited conduction mechanisms of SiO 2 are presently well known. 17 Nitride bulk charge transport has been widely studied in the past.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The change of the slope of the intrinsic distribution does not affect the reliability of the product since the specified lifetime of the product is always in a region of decreasing failure rate for large area capacitors and moreover it is some decades below the intrinsic dielectric lifetime. Distributions measured at different voltages are fitted very well applying equation (5).…”
Section: Modelling Of the Field Dependence For Reliability Predictionsmentioning
confidence: 99%
“…Much of these published reliability results were obtained from planar structures with the bottom-oxide grown on doped poly-Si, which is known to have microstructure and morphology problems (43. The films reported previously were much thicker (8.0-10.0 nm) than the data presented in this work (4)(5)(6)(7). For the first time, this paper describes extensive results for intrinsic breakdown characteristics of reoxidized nitride (NO) dielectric films using deep-trench capacitors with the oxide equivalent thickness (T,) down to 3.9 nm.…”
Section: Introductionmentioning
confidence: 66%